POTENSI NILAI GIZI TERHADAP BAHAYA LOGAM BERAT PADA KEONG MAS (Pomacea canaliculata) DAN KERANG KIJING (Anodonta woodiana) - Hening Widowati; Agus Sutanto; Widya Sartika Sulistiani (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
Pomacea canaliculata and Anodonta woodiana are alternative foods for people who live in Kalibening Village, Pekalongan, Lampung Timur. They live as a filter feeder, so they can accumulate heavy metals Pb and Cd from their habitat potentially. This study aims to determine the effect of cooking method on the levels of Pb and Cd and the nutritional value of P. canaliculata and A. woodiana such as Ca and Protein. The variation of the cooking method that was used in this experiment is: steam, boil and fry with without processing, as a control. Based on the results of the study it is known that boiling is the best method in minimizing Pb and Cd from P. canaliculata and A. woodiana with an average reduction of 41.43% for Pb metal and 58.06% for Cd metal. While the average decrease in Ca levels was around 24.64% and 23.23% for the average reduction in protein.